Relationships between screen time and childhood attention deficit hyperactivity disorder: a Mendelian randomization study - Meng, Zhuo; Ao, Bo; Wang, Wei; Niu, Tongtong; Chen, Yanan; Ma, Xiaoqing; Huang, Youliang (Frontiers in Psychiatry, 2024)
Background In previous observational studies and meta-analyses, childhood attention deficit hyperactivity disorder (ADHD) is found to have a significant association with screen time. However, the causal associations between them remain unclear. Method This study performed a bidirectional two-sample Mendelian randomization (MR) analysis to confirm the causality between screen time and childhood ADHD. Large-scale genome-wide association studies (GWAS) datasets derived from the Psychiatric Genomics Consortium (PGC) and the UK Biobank were used to identify single nucleotide polymorphisms (SNPs) associated with exposure and outcome. Four categories of datasets were selected to represent screen time. The SNPs that are significantly associated with exposure data (P < 5e-08) and have a strong correlation with the exposure in the F-statistic (F > 10) were selected as instrumental variables. This study also used the PhenoScanner V2 database and the LDlink webtool to exclude confounding factors, and the MR-PRESSO method (p < 0.05) was employed to eliminate outliers with bias. Five commonly used methods were employed to assess the interaction and the Inverse Variance Weighted (IVW) method was utilized as the primary basis for determining the MR estimates in this study. Results The MR analysis revealed that the length of mobile phone use (OR, 1.848; 95% CI, 1.3360-2.5558; p=2.07e-4) and the time spent watching television (OR, 2.104; 95% CI, 1.3958-3.1703; p=3.8e-4) increased the risk of childhood ADHD. Although the causal relationships were exclusively identified through the IVW and weighted median methods, the results retained their statistical significance following correction. In the reverse analysis, no evidence was found to support an effect of childhood ADHD on screen time. The sensitivity analysis conducted on the significant findings revealed no evidence of horizontal pleiotropy or heterogeneity. Conclusion This study provides some evidence for the causality of screen time and childhood ADHD. Given the limitations of our study, further research is required to comprehensively investigate this relationship.